CLINICAL MANAGEMENT OF DYSTOCIA DUE TO FETAL ASCITES IN A BUFFALO (BUBALUS BUBALIS) - Kumar, Rajesh; Daund, Sushant Sakhahari; Verma, Sanjeev Kumar; Verma, Abhishek Kumar; Saurabh (Animal Reproduction Update, 2024)
The present communication reports a rare case of dystocia in a four and half  year old she-buffalo due to fetal ascites with posterior presentation, relieved using abdominocentesis and forced traction at veterinary clinical complex, Kumarganj, Ayodhya, UP. The cow was recovered uneventfully.
Keywords: Buffalo; Bubalus bubalis; dystocia; fetal ascites; posterior presentation